2024
DOI: 10.1021/acs.jafc.3c05730
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Antifungal Activity, and Molecular Docking Studies of Novel Chiral Isoxazoline-Benzofuran-Sulfonamide Derivatives

Yingkun Yan,
Ailing Bao,
Yunfan Wang
et al.

Abstract: Succinate dehydrogenase (SDH) is one of the most important molecular targets for the development of novel fungicides. With the emerging problem of resistance in plant fungal pathogens, novel compounds with high fungicidal activity need to be developed, but the study of chiral pesticides for the inhibition of highly destructive plant pathogens has been rarely reported in recent years. Therefore, a series of novel chiral isoxazoline-benzofuran-sulfonamide derivatives were designed to investigate potential novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Molecules containing thioethers and sulfoxides have attracted considerable attention due to their unique physicochemical and physiological properties. These compounds are noteworthy in organic and medicinal chemistry and possess a broad spectrum of bioactivities, including antitumor, , acaricidal, , antifungal, herbicidal, , and antiviral activities. In our research, we discovered and reported that phenyl trifluoroethyl thioether derivatives containing a benzyl group exhibited excellent acaricidal activity, particularly FM-1001 (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Molecules containing thioethers and sulfoxides have attracted considerable attention due to their unique physicochemical and physiological properties. These compounds are noteworthy in organic and medicinal chemistry and possess a broad spectrum of bioactivities, including antitumor, , acaricidal, , antifungal, herbicidal, , and antiviral activities. In our research, we discovered and reported that phenyl trifluoroethyl thioether derivatives containing a benzyl group exhibited excellent acaricidal activity, particularly FM-1001 (Figure ).…”
Section: Introductionmentioning
confidence: 99%